The healthy home : simple truths to protect your family from hidden household dangers - Wentz, Dave (Vanguard Press, 2011)
"Did you know?...We poison our children and pets to kill a fly...We get a dose of antibiotics every day--whether we have a prescription or not...We need Hazmat suits to clean up a broken energy-efficient CFL light bulb. In 'The Healthy Home' father-and-son team Dr. Myron Wentz and Dave Wentz walk readers room-by-room through a typical house, pointing out the surprising health risks posed by everyday products and behaviors of any modern family..."--Dust jacket flap.